Pruning year effects on flying insect diversity and microclimate relationships in Jamus tea agroecosystem, East Java, Indonesia - DWI SUHERIYANTO; YOVITA YUAN SYAHNIAR (Smujo International, 2026)
Abstract. Suheriyanto D, Syahniar YY. 2026. Pruning year effects on flying insect diversity and microclimate relationships in Jamus tea agroecosystem, East Java, Indonesia. Asian J Agric 10 (1): g100134. https://doi.org/10.13057/asianjagric/g100134. Flying insects provide essential ecosystem functions in tea agroecosystems, including pollination and pest regulation. This study examined how the post-pruning recovery cycle influences flying insect communities and microclimate in Jamus tea (Camellia sinensis) plantation. Insects were sampled and microclimate variables (temperature, humidity, light, wind speed) measured across blocks representing the first to fourth years after pruning (PY 1-4). Community metrics and Canonical Correspondence Analysis (CCA) were used to evaluate diversity and habitat associations. We identified 12 insect genera, namely Diabrotica, Altica, Coccinella, Condylostylus, Musca, Syrphus, Sepedon, Taeniaptera, Gonocerus, Lasioglossum, Apanteles, and Amata. Total abundance and genus richness increased with time since pruning, with the lowest diversity and highest dominance in PY 1. Although microclimate did not differ significantly among years, CCA revealed that community composition tracked two environmental gradients: one associated with higher light and wind exposure (linked to genera Lasioglossum and Taeniaptera in later years), and another with cooler, more humid conditions (associated with genera Altica and Sepedon). These findings demonstrate that pruning primarily structures insect communities by modifying physical habitat, rather than altering average plot-level microclimate.